Narrative language abilities in adults with Down syndrome: A remote online elicitation study using the Multilingual Assessment Instrument for Narratives (MAIN) - Mattiauda, Elisa; Hassiotis, Angela; Perovic, Alexandra (Frontiers in Communication, 2022)
Introduction: This research represents, to the best of our knowledge, the first attempt at assessing narrative retell remotely in people with Down syndrome and will provide valuable information on the validity and feasibility of remote online assessment with this population. Most research on language abilities in Down syndrome has focused on children and adolescents, making adults an understudied population. The present research seeks to establish a baseline of functioning for narrative language abilities in adults with Down syndrome, as part of a larger research aiming to investigate possible changes associated with ageing and the emergence of Alzheimer’s disease in this population. Methods: We recruited 13 adolescents and young adults with Down syndrome aged 15-33 years (mean age: 21), matched to a control group of younger typically developing children aged 4-10 years (mean age: 6) on verbal Mental Age (MA). Participants completed a picture-based story retell activity from the Multilingual Assessment Instrument for Narratives (MAIN; Gagarina et al., 2019) and a series of standardised background measures of language and cognitive ability. Results: Our analyses focused on macrostructural indices of narrative performance, narrative length and lexical diversity. Results revealed that our participants with Down syndrome were outperformed by verbal MA-matched controls on measures of story structure and story comprehension, as well as lexical diversity. No difference was found on total number of words, indicating the groups produced comparable amounts of speech despite differences in story grammar and lexis. Discussion: We interpret the results in light of previous research on macrostructural narrative performance in adults and younger adolescents with Down syndrome. Recruitment and data collection outcomes are discussed in terms of successful strategies and possible improvements. We conclude that remote online assessment of people with Down syndrome is feasible, although considerations should be made with regards to facilitating enrolment, and task engagement. Our participants demonstrated ability to engage with the experimenters over video chat and were able to complete the activities proposed mostly independently, with minimal involvement required from caregivers. Recommendations for future remote online studies involving children and people with intellectual disabilities are discussed.